A Joint Scheme for Angle and Array Gain-Phase Error Estimation in Bistatic MIMO Radar - Li, Jianfeng; Zhang, Xiaofei; Gao, Xin (IEEE geoscience and remote sensing letters, 2013)
In this letter, we investigate the subject of joint angle and array gain-phase error estimation for bistatic multiple-input multiple-output radar, and propose a joint scheme for angle and array gain-phase error estimation based on trilinear decomposition. The estimations of transmit and receive direction matrices are primarily obtained via trilinear decomposition, after which the optimization problem for estimating array gain-phase errors and angles can be constructed. Array gain-phase error vectors are obtained by Lagrange multipliers, and the angles are estimated according to the estimated gain-phase errors. In contrast to the ESPRIT-like algorithm, the proposed method not only obtains automatically paired estimations of the angles but also has much better performance for angle and array gain-phase error estimation. Simulations verify the effectiveness of our approach.